Application of several green manures to produce organic cabbage (Brassica oleracea var. Capitata) and their influence on soil biological properties - da Silva Bento, Thatiany; de Carvalho, Marco Antonio Camillo; Yamashita, Oscar Mitsuo; Dallacort, Rivanildo; da Silva, Ivone Vieira; Felito, Ricardo Adriano [UNESP]; de Araújo, Dejânia Vieira (Southern Cross Publishing, 2020)
Green manure stands out in the organic vegetable production as complementary fertilizer alternative to organic compound incorporation, contributing to reduce production costs and improve soil physical, chemical and biological features. The aim of the current study is to assess green manure and spontaneous vegetation species in cropping systems focused on the organic cabbage production, as well as their influence on soil microbial community. The treatments consisted of green manures such as black velvet beans (Stizolobium aterrimum), Crotalaria spectabilis, jack beans (Canavalia ensiformis), pigeon peas (Cajanus cajan cv. Iapar 43) and spontaneous vegetation (fallow) in two cropping systems (with and without incorporation of green manure plants). Evaluations of green manure, cabbage crop and soil microbial activity were carried out. Green manure: fresh and dry mass, nitrogen and accumulated nitrogen content; Cabbage culture: horizontal and vertical diameter of the head, commercial and total mass; Microbial soil activity: soil microbial biomass carbon, soil basal respiration and metabolic quotient. For fresh and dry mass, jack beans and pigeons pea presented higher values, indicating good performance of these materials. For both, nitrogen content and accumulated nitrogen, the jack beans were stood. Regarding cabbage culture, the spontaneous vegetation decreased the horizontal diameter of the head when the incorporation did not occur. As for the commercial mass, for jack beans the cultivation with incorporation was superior. When the incorporation of the covering plants occurred, the crotalaria spectabilis produced less commercial mass and total head mass. Still in relation to total head mass, jack beans and spontaneous vegetation had lower mass when no incorporation occurred. As to soil microbial biomass carbon the spontaneous vegetation presented higher value, differing only from black velvet beans. The use of jack beans as a cover crop associated with the incorporation system was shown to be promising for the production of cabbage.
Keywords: Cajanus cajan; Canavalia ensiformis; cropping systems; Crotalaria spectabilis; nitrogen content; spontaneous vegetation; Stizolobium aterrimum; weeds